THE ROLE OF RELIGIOUS SCIENTISTS DURING THE RULE OF SULTAN HUSAYN BAYQARA (Scientific journal of the Fergana State University, 2024)
This article contains information about the history of the rise to power of Sultan Husayn Bayqara, one of the brightest representatives of the Timurid Empire, economic and political processes in Khorasan and Mavrennakhr, as well as the reforms he carried out to change state and public life. for the better. The religious scholars active during the reign of Sultan Husayn Bayqara, their level of influence in society, and their role in the palace and beyond were also studied. It is stated that during the Timurid period, religious scholars consulted the council of theologians on any important issue or when making laws and decisions affecting the entire country, as well as on the question of the intervention of religious scholars in political processes. During the study, we see that religious scholars enjoyed high authority in the Sultanate, and the rulers constantly communicated with them and gave advice.